Implementation of the Sugeno Fuzzy Method in a Firefighting Robot Prototype with an All-Wheel Drive System - Sutarmin; Ajar Rohmanu; Endang (International Journal Software Engineering and Computer Science (IJSECS), 2024)
The purpose of this study is how to implement the Fuzzy Sugeno method to a fire-fighting robot prototype with all wheel drive system. Resculpts by transferring academic input to specific fields of knowledge, as many problems have become increasingly adaptable due to technology or the growth of AI, which is fast becoming the dominant productivity tool. Fuzzy method is a mathematical method used to overcome the problems of small uncertainties and imprecision. The first prototype of the fire-fighting robot which will be able to use all-wheel drive system is meant to mitigate the risk of large fire and to detect as soon as possible. Observational results verify that the Robot prototype follows its intended workflow as well as can complete its mission to both detect and eliminate fire hazards. The speed of the wheel is controlled on three levels slow (0 RPM), moderate (50 RPM), and fast (100 RPM) using Fuzzy Sugeno method. Also, in response time is set by using Fuzzy Sugeno method which is set to 1 second, 2 seconds, and 3 seconds